2003
DOI: 10.1103/physrevlett.90.077201
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of Co-Fe Binary Alloy Monolayers on W(110)

Abstract: We present an experimental investigation of CoxFe1-x monolayers grown on flat and stepped W(110) surfaces. Atomically resolved scanning tunneling microscopy and low energy electron diffraction reveal continuous miscibility and pseudomorphic growth of Co and Fe for 0 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…In that case the authors observed a monotonically decreasing Curie temperature with increasing the Co concentration. 46 This was ascribed to the Fe-Co hybridization which, in this peculiar system, reduces the tendency toward ferromagnetic ordering with increasing Co content.…”
Section: Continuous Fe X Co 1−x Films: Coercivity Versus Stoichiommentioning
confidence: 99%
“…In that case the authors observed a monotonically decreasing Curie temperature with increasing the Co concentration. 46 This was ascribed to the Fe-Co hybridization which, in this peculiar system, reduces the tendency toward ferromagnetic ordering with increasing Co content.…”
Section: Continuous Fe X Co 1−x Films: Coercivity Versus Stoichiommentioning
confidence: 99%
“…At an intermediate temperature (510 K) one even obtains ordered alloy structures as shown by LEED (see Fig. 6) and STM [9]. However, the comparatively large width of the superstructure spots observed by electron diffraction indicates that the order in this case is of short-range nature.…”
Section: Article In Pressmentioning
confidence: 82%
“…Deposition of small amounts of Co at room temperature followed by annealing leads to a fundamentally different morphology in comparison to the deposition at high substrate temperatures. In contrast to sequential deposition a codeposition of both elements results in an ordered or random alloy depending on the growth temperature [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The W(1 1 0) crystal consisted of a flat and a vicinal part with atomic steps along the [0 0 1] direction and a terrace width of 9:1 nm: The alloy films with a thickness of 1.8-7 monolayer (ML) were deposited at room temperature. Pseudomorphic growth and continuous miscibility of Co x Fe 1Àx monolayers was shown for xo0:6 by scanning tunneling microscopy (STM) and low energy electron diffraction (LEED) [5]. Higher Co concentrations led to a phase separation of Co-rich segregations, which are grown in Nishiyama-Wassermann orientation on the substrate.…”
mentioning
confidence: 97%